Aligning steel fibers in cement mortar using electro-magnetic field. (30th January 2017) - Mu, Ru; Li, Hui; Qing, Longbang; Lin, Jianjun; Zhao, Quanming
Highlights: A detailed approach of aligning steel fibers in cement mortar using magnetic field was presented. Necessary magnetic induction of magnetic field and workability of fresh mortar for aligning steel fiber were suggested. X-ray CT test results showed that the steel fibers in hardened mortar was highly aligned. Aligned steel fibers significantly increase the efficiency of reinforcement on mortar. Abstract: An approach of aligning steel fibers in cement mortar using external uniform electromagnetic field is presented, which is the rotating process of steel fiber driven by magnetic force to overcome the viscous impeding of the mortar. Using the approach, the aligned steel fiber reinforced cement mortar (ASFRC) is prepared. Then the orientation distribution of the steel fibers in ASFRC is measured by X-CT image analysis. The results show that the orientation efficiency factor of the steel fibers in ASFRC reaches around 0.90, while that of ordinary steel fiber reinforced cement mortar (SFRC) is around 0.50. Also, the splitting tensile strength, flexural strength and toughness of the ASFRC are tested. The test results show that, compared with SFRC, the splitting tensile strength and flexural strength of ASFRC increase up to more than 100%, which is attributed to the increase in reinforcing efficiency of aligned steel fibers.